2019
DOI: 10.1002/acm2.12624
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of pharamcokinetic DCE‐MRI and IVIM‐DWI could improve detection efficiency in early diagnosis of ductal carcinoma in situ

Abstract: Purpose Ductal carcinoma in situ (DCIS) is a precursor of invasive ductal breast carcinoma (IDC). This study aimed to use pharamcokinetic dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) and intravoxel incoherent motion diffusion‐weighted imaging (IVIM‐DWI) for the early diagnosis of DCIS. Methods Forty‐seven patients, including 25 with DCIS (age: 28–70 yr, mean age: 48.7 yr) and 22 with benign disease (age: 25–67 yr, mean age: 43.1 yr) confirmed by pathology, underwent pharamcokinetic DCE‐MRI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…However, non-mass DCIS may represent a pitfall for DWI detection [35,36], as in this our false-negative case. Interestingly, Tao et al [37] recently reported on intravoxel incoherent motion, i.e., the new DWI analysis model with more than two b values, to be helpful for the early diagnosis of DCIS, preventing missing malignant diagnosis, and overtreatment of benign lesions. In our study, all but one false negatives were non-mass lesions with a resultant promising and interesting 76% sensitivity of DWI for non-mass cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, non-mass DCIS may represent a pitfall for DWI detection [35,36], as in this our false-negative case. Interestingly, Tao et al [37] recently reported on intravoxel incoherent motion, i.e., the new DWI analysis model with more than two b values, to be helpful for the early diagnosis of DCIS, preventing missing malignant diagnosis, and overtreatment of benign lesions. In our study, all but one false negatives were non-mass lesions with a resultant promising and interesting 76% sensitivity of DWI for non-mass cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The signal intensity kinetics acquired by DCE-MRI suggest the underlying microvessel density, perfusion, permeability, and the extracellular-extravascular space composition of tumors (Zahra et al, 2007;Bonekamp et al, 2016). DCE-MRI can predict the response to and outcomes of radiotherapy in patients with cervical cancer (Tao et al, 2019). Tao et al reported (2019) that the K trans of high-grade ductal carcinoma in situ of the breast is higher than that of low-grade ductal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Tao et al [32] made with only DCIS lesions, they found that most middle and high-grade DCIS lesions showed non mass like enhancement so it is hard to be recognized by DWI. They used DCE-MRI and intravoxel incoherent motion DWI (IVIM-DWI) and reduce the misdiagnosis of DCIS.…”
Section: !"#$%Andb(and!/%and#%+and14c-77and="$4%+and7-3and$%+*-5and""...mentioning
confidence: 99%
“…We thought maybe we could hardly find DCIS lesions and ADC and r ADC values were not truly evaluated. Maybe a study using IVIM, DWI must be done and evaluate ADC and r ADC value with this technique [32].…”
Section: !"#$%Andb(and!/%and#%+and14c-77and="$4%+and7-3and$%+*-5and""...mentioning
confidence: 99%